THE MARKET POWER OF TURKEY'S IMPORTED TOBACCO MARKET - Yrd. Doç. Dr. Kübra Önder (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
Despiteits high share in the taxes collected and the superiority in foreign trade,tobacco production has been regulated by special laws for many years due to theincreased production of tobacco to the detriment of other agricultural productsand the large number of producers. Public supervision, regulation andsurveillance are still in progress despite the major changes experienced in thetobacco market due to the recent changes in legislation. Tobacco productioncannot be increased because of technological insufficiency and inadequatedevelopment of research activities. As well as this, there is an increase in thedemand for imported tobacco, which is relatively cheaper than domestic tobaccoin the global competitive environment. This is what transforms Turkey's marketposition into the largest tobacco importer which was a tobacco exportingcountry before. The aim of this study isto calculate Turkey's market power in the tobacco import market econometricallyby using New Industrial Organization method. Market power coefficient was foundto be 0.37 in this study in which annual data for the period 1994-2016 were used.This result reveals that Turkey's tobacco import is not realized under perfectcompetition conditions and the firms display behaviors in oligopolisticstructure.